Survey of Pest Management Practices on US Golf Courses - Travis W. Shaddox; J. Bryan Unruh; Mark E. Johnson; Clark D. Brown; Greg Stacey (HortTechnology, 2023)
Integrated pest management (IPM) is an important component of golf course maintenance and includes conventional chemical pesticide use as well as nonchemical cultural management practices. Determining how frequent pest management practices are used on golf courses is critical when developing educational and outreach programs. The objective of this study was to determine the frequency of pest management practices and pesticide mixing and storage facilities on US golf courses. A survey was sent to 14,033 operational US golf facilities with 10% responding. Reliance on all conventional chemical pesticides increased from 2015 to 2021. The reliance on biological control products declined to 14% and reliance on the nonpesticide practice of using plant growth regulators remained equivalent to 2015. The most common pest management practices included monitoring weather patterns and scouting for pests, with 93% of golf facilities reporting the use of both. The use of written IPM and pesticide application plans increased from 44% to 63% of golf facilities between 2015 and 2021, respectively. Generally, mixing and storage facilities remained unchanged from 2015 to 2021. US golf facilities continue to use nonchemical pest management practices, but reliance on chemical pesticides has increased.